2022
DOI: 10.1177/03000605221084874
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of mean platelet volume in patients with lung cancer: a meta-analysis

Abstract: Objective The mean platelet volume (MPV) is a measure of platelet size, and it is considered a surrogate marker of platelet activation. Because the correlation between platelet count/size and lung cancer prognosis remains unclear, this meta-analysis comprehensively evaluated the prognostic significance of MPV among patients with lung cancer. Methods A systematic search of PubMed, Embase, Google Scholar, and additional sources of relevant studies were conducted with no language restrictions from inception to 7 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…More particularly, most studies in colon cancer (4 out of 6) and fewer in lung cancer (4 out of 10) indicated an unfavorable role of increased MPV regarding mortality. It is noted that MPV was not related to overall survival in a recent meta-analysis of lung cancer patients [ 26 ]. As far as other cancer types are concerned, fewer studies were conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More particularly, most studies in colon cancer (4 out of 6) and fewer in lung cancer (4 out of 10) indicated an unfavorable role of increased MPV regarding mortality. It is noted that MPV was not related to overall survival in a recent meta-analysis of lung cancer patients [ 26 ]. As far as other cancer types are concerned, fewer studies were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are few reviews on the relationship between MPV and cancer; including studies up to 2015, Ref. [ 24 ] is a recent review that has evaluated platelet indices with esophageal squamous cell carcinoma [ 25 ], and it includes a meta-analysis of 2421 patients, which has focused on the relation of MPV to survival in lung cancer patients [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study of 496 NSCLC patients at stages IIIB/IV showed that a high level of MPV is associated with shorter OS (Omar et al 2018 ). On the other hand, a recent meta-analysis of 2,421 patients with NSCLC from 11 publications revealed no significant associations of MPV with OS and PFS (Kharel et al 2022 ). It must be, however, noted that none of the included studies was prospective, and that the meta-analysis did not specify differences between different types of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of poor prognosis for lower MPV measured at diagnosis [ 31 , 32 ] may be more relevant to our findings because these are based on prospective studies and reflect lung cancer progression, which may involve pathways relevant to lung cancer development. Cancer survival, however, is dependent on comorbidities related to platelet activity, as well as on cancer progression and metastasis, and a large meta-analysis has found little evidence for association of MPV measured at diagnosis with overall survival [ 33 ]. Our findings are compatible with a small scale study reporting higher PDW at lung cancer diagnosis [ 15 ], but only for men.…”
Section: Discussionmentioning
confidence: 99%